Sprawozdanie z cyklu wykładów PBPO „Orient Daleki i Bliski" - Sadowa, Katarzyna; Spychalska, Aleksandra (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The series of lectures entitled ‘Orient Daleki i Bliski’ was launched in 2013 form the initiative of prof. M. Sadowski. Since then, it has generated a lot of interest. A part in the events is being took not only by the students from University of Wroclaw and the Faculty of Law, Administration and Economics, but also people outside this academic center. In this report the authors will present the particular lectures given during three series of ‘ODiB’
Keywords: Pracownia Badań Praw Orientalnych; wykłady; prawo orientalne; Japonia; Chiny; islam; sprawozdania